2011
DOI: 10.1371/journal.pone.0014653
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Two-Component System Sensory Kinase DegS Is Regulated by Serine Phosphorylation in Its Input Domain

Abstract: Bacillus subtilis two-component system DegS/U is well known for the complexity of its regulation. The cytosolic sensory kinase DegS does not receive a single predominant input signal like most two-component kinases, instead it integrates a wide array of metabolic inputs that modulate its activity. The phosphorylation state of the response regulator DegU also does not confer a straightforward “on/off” response; it is fine-tuned and at different levels triggers different sub-regulons. Here we describe serine pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…The DegS domain (residues 12 to 170), with an unknown function, is another candidate site regulating the interaction. Although the physiological significance is obscure, Ser76 in this domain is phosphorylated in vivo, and YbdM was proposed previously to be a kinase responsible for Ser76 phosphorylation (11). The expression of the pgs operon is regulated not only by cell density but also by nutritional signals from the environment (13).…”
Section: Discussionmentioning
confidence: 99%
“…The DegS domain (residues 12 to 170), with an unknown function, is another candidate site regulating the interaction. Although the physiological significance is obscure, Ser76 in this domain is phosphorylated in vivo, and YbdM was proposed previously to be a kinase responsible for Ser76 phosphorylation (11). The expression of the pgs operon is regulated not only by cell density but also by nutritional signals from the environment (13).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DegS was found to be phosphorylated on residue Ser76, situated in its signal-sensing domain (Macek et al, 2007). Jers et al (2011) demonstrated that DegS Ser76 can be phosphorylated by two B. subtilis STKs: PrkD (YbdM) and YabT (Fig. 3a).…”
Section: Phosphorylation Of Tcs Hks and Rrs By Stksmentioning
confidence: 94%
“…They are also involved in spore development via phosphorylation of a recombinase RecA (7), in spore germination (8), and in regulation of the general stress sigma factor SigB via phosphorylation of Rsb-proteins (9). Importantly, Ser/Thr kinases can also regulate complementary signal transduction systems as shown by phosphorylation of the two-component kinase DegS (10). In addition, B. subtilis tyrosine kinase PtkA plays an important role in DNA replication by phosphorylating SSB proteins (11,12).…”
mentioning
confidence: 99%